Density, damage and distribution of Cucullia calendulae (Noctuidae) in patches of Calendula arvensis - PÉREZ-GUERRERO, SERGIO; REDONDO-VILLA, ALBERTO JOSÉ; TORRES-PORRAS, JERÓNIMO (Revista Colombiana de Entomología, 2010)
Most studies on the family Noctuidae focus on very few species that cause damage to crops; however, there is little information on the biology and ecology of the remaining species of noctuid moths. This work examines the relationship of the larvae of Cucullia calendulae with their main food plant Calendula arvensis. The results showed that the larvae of this species feed on the fruiting bodies, reaching an overall incidence of ca. 30%. In addition, there was a differential distribution of larvae according to their size. Early stages were found in the reproductive structures while latter stages were found on the stems, which should be due to a defensive strategy. Furthermore, from seven characteristics of the patch taken into account, only the height of the plant explained a greater number of larvae per patch.